Heaven official's blessing, manhua. Volume 3 - Moxiangtongxiu (Aloha Comics, 2025)
"The prince had entirely forgotten that it was the eve of the Hungry Ghost Festival when he set out on his journey. On this night, one risks wandering into the Ghost Realm without a chance of returning. Narrowly escaping vengeful spirits, Xie Lian and San Lang make it to Puqi, the Village of Water Chestnuts. But before they can restor tidy up the shrine, a frantic Taoist arrives with a plea for aid."--